Correction: Sustained delivery of anti-VEGF from injectable hydrogel systems provides a prolonged decrease of endothelial cell proliferation and angiogenesis in vitro. Issue 29 (1st May 2018) - Fletcher, Nathan A.; Krebs, Melissa D.
Abstract : Correction for 'Sustained delivery of anti-VEGF from injectable hydrogel systems provides a prolonged decrease of endothelial cell proliferation and angiogenesis in vitro ' by Nathan A. Fletcher et al., RSC Adv., 2018, 8, 8999–9005.